Електронний уряд (e-government) і електронне урядування (e-governance): поняття та принципи функціонування - Погребняк, І. Є. (Право, 2014)
Статтю присвячено: аналізу понять «електронний уряд» та «електронне урядування», а також принципам функціонування електронного уряду. Проаналізовано структуру концепції електронного уряду, дано характеристику основним елементам концепції. Електронний уряд є незмінною характеристикою країн, які активно розвиваються. Немалу роль в стрімкому розвитку економік таких країн відіграє оптимізація процесу управління, підвищення його ефективності – результат впровадження практики електронного уряду. // The article is devoted to: Analysis of the concepts "Electronic Government" and "Electronic Governance", as well as the principles of functioning of the electronic government. The structure of the concept of the electronic government is analyzed, the characteristics of the main elements of the concept are given. The electronic government is an unchanged characteristic of countries that are actively developing. An important role in the rapid development of economies of such countries plays optimization of the management process, increasing its efficiency - the result of the implementation of the practice of e-government.
Keywords: електронний уряд; електронне урядування; ефективне урядування; e-government; e-governance; government; governance; electronic government; effective governance